Efficacy of NaCl nebulized hypertonic solutions in cystic fibrosis - Manca, A.; Difino, V.; Urbano, F. (Acta Biomedica Atenei Parmensis, 2014)
Introduction: CFTR deficiency produces poor water secretions. We studied the effects of nebulized hypertonic solution. Methods: 30 CF patients, each patient considered a control of himself, were followed to evaluate the therapeutic efficacy by spirometric indices. Outcomes: Results, statistically significant, indicate best results for small/medium airways. Conclusion: Nebulized hypertonic saline achieves the best results in heterozygous F508del, BCC negative, BMI>5th